Significance of IgM anti-HCV core level in chronic hepatitis C - Papatheodoridis, G. V.; Delladetsima, J. K.; Katsoulidou, A; Sypsa, V; Albrecht, M.; Michel, G.; Hatzakis, A; Tassopoulos, N. C. (J HepatolJournal of Hepatology, 1997)
AIM: To investigate the significance of IgM antibody to hepatitis C virus (HCV) core antigen (IgM anti-HCV core) in chronic hepatitis C. METHODS: In a group of 112 patients with histologically proven chronic hepatitis C positive for HCV RNA, IgM anti-HCV core level was studied by a sensitive semi-quantitative enzyme immunoassay. Quantitation of serum HCV RNA was done by a second generation bDNA assay and determination of HCV genotype by RT-PCR and reverse hybridization. RESULTS: IgM anti-HCV core was detected in 72 (64.3%) of the 112 patients. ALT levels were significantly higher in IgM anti-HCV core positive than negative patients. No other significant difference was observed in any of the patients' characteristics between IgM anti-HCV core positive and negative groups. On the contrary, IgM anti-HCV core level was found to be significantly higher in females than in males, in patients with moderate or severe chronic hepatitis, in patients with high HCV RNA levels and in patients infected with HCV genotype 1b. Moreover, IgM anti-HCV core level was significantly correlated with age and ALT level. Multiple regression analysis showed that IgM anti-HCV core level was significantly related only to the HCV genotype (p=0.001), histological grade (p=0.017) and ALT level (p=0.038). CONCLUSIONS: Our data support the hypothesis that IgM anti-HCV core level is associated mainly with HCV genotype and secondly with liver disease necroinflammatory activity. These associations may have implications in the pathogenesis of chronic hepatitis C.
Keywords: Adult; Aged; Aged, 80 and over; Chronic Disease; Female; Genotype; Hepacivirus/genetics/*immunology; Hepatitis C Antibodies/*blood; Hepatitis C Antigens/*immunology; Hepatitis C/blood/*immunology/pathology/virology; Humans; Immunoglobulin M/*blood/immunology; Liver Cirrhosis/pathology; Male; Middle Aged; RNA, Viral/blood; Severity of Illness Index; Sex Factors; Viral Core Proteins/*immunology